Avaliação de um programa de resposta à intervenção multinível para estudantes com dificuldades de aprendizagem - Machado, Andréa Carla (2014)
The model of Response to Intervention ( RTI ) is a multilevel program for the early identification of possible delays academics directed at students who have learning difficulties that require more specific interventions. In this sense, the present work aimed to develop , implement and evaluate a program of Response to Intervention ( RTI ) for students with Learning Disabilities and their teachers and families. This is a quasi- experimental research design collaborative nature, whose investigative path was qualitative / quantitative design with pre -test -intervention - post -test - Tracking. To do so, data were collected through thirteen instruments distributed among the participants. The study included 14 ( fourteen) students nominated by their teachers , with 30 % female and 70 % male , with a mean age ( M = 9.07 ) years of age, inserted in an ordinary classroom of 3 ( 29 % ) , 4 ( 71 % ) year of elementary school ; The six participating teachers are belonging to two public schools , with a mean age ( M = 41.1 ) and, which give classes in 3rd and 4th year of elementary school , being belonging to four teachers and two school I II school , all teachers were female presented with a mean length of experience ( M = 13.1 ) and; the researcher with 38 years at baseline and academic career related to special education ; The study also involved the fourteen families of students participating in the research , whose level of education of household head ranged from illiterate to complete high mean age ( M = 35.2 ), 50% of households not fit the criteria socioeconomic classification of Brazil , class D , and 28 % in the C2 class. It was found that the families studied belong to a scenario economically disadvantaged. The research was conducted in two public schools in a regular municipal public belonging to a city in the state of São Paulo. The spaces were the classrooms of participating teachers , extending into other school spaces , such as meetings between the researcher and teachers was conducted in a room for pedagogical support imparted by coordination of schools. The rooms belonging to the target students were on average 15 to 20 students each. The program proceeded with a plan of action in three levels ( called RTI - Response to Intervention ) , from the knowledge of the needs of the students and their teachers ; involved the establishment of a partnership with systematic support among teachers in twenty fortnightly meetings , and reflection on practice activities , and attendance of students : Level I of the RTI ( this program also applied to collaborative consultation for teachers ) refers to the implementation of the activities developed by the researcher and teachers and applied by teachers themselves for all students in the context of the classroom with an alternating schedule during the week for implementation of activities during the 2011 school year , at this stage ( level RTI ) all attended school , ie 14 each in his room with his teachers ; RTI Tier II compliance against shift of target students divided into small groups that did not receive advance after receiving appropriate interventions at the level I of RTI conducted by the researcher with a 1 hour two hours a week for four (4 ) weeks. In this step through the program five students of the fourteen indicated at baseline ; and RTI -III for students who did not achieve good performance after the sessions relating to level II also carried out by the researcher and lasted for one hour, four times a week for two (2 ) weeks. At this stage , only two students were subjected to the intervention of the five school referring to earlier in the RTI program. Thus , of the fourteen students nominated for the RTI program , only two schools have not responded , or failed after receiving specific interventions and participation levels of the program. Compared to parents of targeted students five fortnightly lectures were given to assist them in relating to the academic life of their children during the months of April and May 2012 pipes. Data were collected on before and after the intervention time of follow-up , which was performed thirteen months after the pretest and four months after the post-test time. Quantitative data were analyzed according to specific criteria of the instrument and applied to descriptive statistics. The qualitative data were analyzed according to three the proposed content analysis. The data obtained before and after the intervention were compared with follow-up time to check the efficiency and effectiveness of activities undertaken during the consultancy provided. Fredman 's test was applied to verify the differences between the three moments of the variables , also the test of Wilcoxon Signed Posts Bonferroni adjusted for correlation to identify which time points ( Pre , Post and Follow-up testing ) differentiate themselves me ; Kendall test for possible differences between the three time points, when compared concurrently to the variables of interest for each task ; To verify the existence of a relationship between variables : academic / behavioral performance ; academic / parenting style performance Test Analysis Spearman correlation was used in each observation time , pre-and post -test , and the test was applied Cronbach's alpha statistic for checking the level of reliability / agreement. The results indicate a positive effect with regard to the RTI program developed and the first associated with teachers using the model of collaborative consultation and a statistically significant difference when comparing the preoperative data , post and follow-up time. Noticed a social validity when responses on satisfaction of teachers and parents about the program offered were obtained. In the same way , we can see that there were positive results in relation to instruments applied at the beginning and end of the RTI program. We conclude that all of these aspects seem to demonstrate the impact of developing collaborative nature programs in schools , whose interventions can encourage students in different aspects , such as in this study , academic and behavioral. This research presented in accordance with the results obtained regarding the effectiveness and efficiency of the program RTI developed. However , we highlight some limitations , which may be revised and scaled for future research in the area , it is because this work is the first in the Brazilian territory related to Response to Intervention Model ( RTI ).